2001
DOI: 10.1093/jac/47.6.755
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane protein change combined with co-existing TEM-1 and SHV-1 beta-lactamases lead to false identification of ESBL-producing Klebsiella pneumoniae

Abstract: Nine isolates of Klebsiella pneumoniae, obtained from one colonized and eight bacteraemic patients on a paediatric ward, were shown to be identical by PFGE, indicating an outbreak. Screening for extended-spectrum beta-lactamase (ESBL) production using the double-disc synergy test, Etest for ESBLs and agar diffusion tests indicated ESBL production. The isolates showed reduced susceptibility to cefotaxime but not to other third-generation cephalosporins. Molecular studies revealed production of TEM-1 and SHV-1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Wu et al (2001) found that decreased outermembrane permeability, due to loss of outer-membrane protein K35 (OmpK35), and the hydrolytic effect of TEM-1 can increase the MIC of cefotaxim slightly. The addition of clavulanic acid inhibits TEM-1 b-lactamase production and reduces the MIC, causing augmentation of the inhibition zone diameter, resulting in a false-positive ESBL test result (Beceiro et al, 2011;Robberts et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2001) found that decreased outermembrane permeability, due to loss of outer-membrane protein K35 (OmpK35), and the hydrolytic effect of TEM-1 can increase the MIC of cefotaxim slightly. The addition of clavulanic acid inhibits TEM-1 b-lactamase production and reduces the MIC, causing augmentation of the inhibition zone diameter, resulting in a false-positive ESBL test result (Beceiro et al, 2011;Robberts et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…All discs were purchased from Biorad (France). The procedures and interpretation of the double-disc synergy test were described previously 12 .…”
Section: Antibacterial Tests Confirmatory Test For Esbl-producing K mentioning
confidence: 99%
“…Of the four clinical isolates of K. pneumoniae and E. coli, two were confirmed to be ESBL producing isolates by the double disc synergy test according to Wu et al 12 . Double-disc tests showed synergy for co-amoxiclav with cefotaxime, aztreonam and cefepime against both E. coli (no.…”
Section: Confirmatory Testmentioning
confidence: 99%
“…plasmid Mini Kit I (Omega Bio-Tek, USA). The presence of plasmid extended-spectrum betalactamase genes was confirmed by polymerase chain reaction (PCR), using gene specific primers as described in the literature (Edelstein, Pimkin, Palagin, Edelstein, & Stratchounski, 2003;Wu et al, 2001). These PCR products were analyzed using 2% agarose gel.…”
Section: Genetic Analysismentioning
confidence: 99%